2015
DOI: 10.1007/s10900-014-9981-0
|View full text |Cite
|
Sign up to set email alerts
|

A Global Health Elective for US Medical Students: The 35 Year Experience of the State University of New York, Downstate Medical Center, School of Public Health

Abstract: The School of Public Health at the State University of New York, Downstate Medical Center has sponsored a 6-8 week global health elective for fourth year medical students since 1980. The purpose of this elective is to provide students with an opportunity to observe the health care and public health delivery systems in low-income countries, provide medical service and have a cross-cultural experience. Over the course of the past 35 years, 388 students have participated in this global health elective in more tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 8 publications
0
31
0
Order By: Relevance
“…This is consistent with another study of US medical students, which found that a 1-week trip was sufficient to stimulate students' interest in GH and encourage future longer-term efforts. 16,26 However, care should be taken when interpreting this finding. Although increasing GHE duration may not translate directly into increased GH interest, GHEs serve various purposes aside from simply stimulating student interest in GH careers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is consistent with another study of US medical students, which found that a 1-week trip was sufficient to stimulate students' interest in GH and encourage future longer-term efforts. 16,26 However, care should be taken when interpreting this finding. Although increasing GHE duration may not translate directly into increased GH interest, GHEs serve various purposes aside from simply stimulating student interest in GH careers.…”
Section: Discussionmentioning
confidence: 99%
“…However, this finding contrasts with another study wherein increasing age was associated with decreasing GH interest. 15 The difference in these findings may result from population differences-Nathan et al 15 studied OB/GYN residents rather than medical/nursing students 16 -and it may be that as health care train-ees progress to these more advanced stages of training, increasing age becomes a restricting factor in one's GH interest because of an increased focus on clinical medicine and career development. Direct comparisons with this study are further limited because their questionnaire addressed interest in a GH elective and perceived GH importance rather than GH career interest.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In medicine specifically, there is consistent evidence for the educational and personal benefits of IHEs in both pre‐certification and early post‐practice settings, as well as their broader value for the health care system. A number of qualitative and quantitative evaluations, including those comparing medical students who have undertaken IHEs with those who have not, have shown the positive impact of IHEs on personal consultation, clinical and diagnostic skills; 3 , 9 , 10 significantly higher average scores in the preventive medicine and public health portions of the National Board of Medical Examiners assessments; 11 and a greater appreciation of the importance of public health, health service delivery and cross‐cultural communication 3 , 9 . ‐ 12 Further, an increased appreciation of the role of primary care and the importance of addressing the unmet needs of under‐served communities is demonstrated by the career destinations of these graduates 3 , 10 …”
Section: The Value Proposition Of Global Experiencesmentioning
confidence: 99%
“…3,[9][10][11][12] Further, an increased appreciation of the role of primary care and the importance of addressing the unmet needs of under-served communities is demonstrated by the career destinations of these graduates. 3,10 Many global student experiences take place between two developed countries. While these IHEs have advantages in terms of risk minimisation for students, they can limit the potential benefits that might present with experiences in developing countries.…”
Section: Market Forces and Increasing Demand For International Healthmentioning
confidence: 99%